Ecosystem Cards: Deepen your understanding of the status quo. Envision desirable futures. Design strategic experiments to learn more - and Lukyanova, Zoya; Polok, Darius; Shah, Indira; Martin, Naomi; Kildeev, Ruslan (resense360 & iac Berlin, 2025)
A tool to deepen your understanding of the status quo, envision desirable futures, and engage with ecosystems more intentionally.